DETERMINAN KETAHANAN PANGAN RUMAH TANGGA MASYARAKAT MUSLIM DKI JAKARTA - Kahfi Auriza Syaman (2023)
There is an increase in the Muslim population of DKI Jakarta, this is related to population density which can affect the quality of life of its residents. In areas with high densities, efforts to improve the quality of the population will be more difficult to carry out and this raises problems of food demand and security. This study aims to explain the determinants of the resilience of Muslim communities. The population in this study is the people of DKI Jakarta. Sampling with non-probability sampling with purposive sampling. This study used 180 respondents according to the criteria of the Muslim population of DKI Jakarta who are of productive age. The approach used is quantitative. The technique of collecting data in this study uses a questionnaire. Data analysis technique using PLS. The results of the hypothesis test are that income has a positive effect on food security, education has a positive effect on food security, and the number of family members has no effect on food security.